Construction and Characterization of an lpxM-Deficient Acinetobacter baumannii Strain Using a pyrF/5-FOA Counterselection System - Gao C; Jiang K; Qi J; Zheng C; Liang Y (Infection and Drug Resistance, 2025)
Can Gao,* Kun Jiang,* Jiaxin Qi,* Chang Zheng, Yanli Liang Department of Clinical Laboratory, Suining Central Hospital, Suining, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanli Liang, Email liang_li0116@163.comAim: Multidrug-resistant Acinetobacter baumannii (MDR-AB) is on the rise, making it challenging to achieve the desired therapeutic effects with existing conventional antibiotics. The search for new antibacterial targets has emerged as a significant research focus.Purpose: The lysophospholipid acyltransferases (LPLATs) proteins encoded by the lpxM gene play a pivotal role in the biosynthesis of lipopolysaccharides (LPS). LPS is a critical component of the outer membrane of the cell wall and is essential for the survival and drug resistance of Gram-negative bacteria. This study aims to investigate the effects of the lpxM gene on the growth and drug susceptibility of MDR-AB.Methods: The standard strain of Acinetobacter baumannii (A. baumannii, AB) AYE was selected as the target. The lpxM gene was knocked out using the pyrF/5-FOA-based counterselectable method. Subsequently, the growth status and the minimum inhibitory concentration (MIC) of the knockout strain against conventional antibiotics were compared.Results: The lpxM gene in AB AYE was successfully and fully knocked out. The absorbance value at OD600 for the lpxM knockout strain during the stable period was observed to be as low as 2.5, indicating a significant reduction in growth rate. Furthermore, the MIC of the knockout strain for imipenem decreased from 16 μg/mL to 1 μg/mL, and the MIC for ceftazidime decreased from 32 μg/mL to 16 μg/mL, enhancing antibiotic sensitivity.Conclusion: This study demonstrates that the deletion of the lpxM gene induces alterations in the growth and drug resistance of AB, providing a crucial foundation for further investigation into the mechanisms underlying LPS-mediated drug resistance and for the screening of effective auxiliary inhibitors targeting lpxM against MDR-AB.Keywords: Acinetobacter baumannii, lpxM gene, pyrF/5-FOA, nutritional deficiencies, lipopolysaccharide